Bridging the gap between academia and practice: novel organogram at the Pharmacy Council of India - Mansi Doshi; Minesh Parbat; Vibhu Paudyal; John Marriott (Taylor & Francis Group, 2022)
Harm with inappropriate and irrational use of medications is a global challenge. The need for and patient access to medicines optimisation services is apparent globally and amplified in India due to multiple reasons. Clinical pharmacists are ideally placed to promote patient safety with medicines use optimisation and other pharmaceutical care services through appropriate legislative, policy, and compensation mechanisms to achieve optimal patient outcomes. The need is for a move at a global level, an enabling organisational structure at Pharmacy Councils and in practice regulations, particularly in countries where clinical roles are still in infancy. This narrative describes the current status and future needs for development of medicines optimisation services across sectors through regulatory and organisational reforms at the Pharmacy Council of India with additional registration, continuing professional development, renewal and licensing requirements for clinical pharmacists to respond to patient and societal needs in India.